Proposed Model for the Construction of the University of Al-Balqa’ Applied e-Learning System Using Web Engineering Standards - Ahmad Hamzah, Hussin; Sadry Abu Seman, Muhamad (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper aims to use web engineering to establish a suitable e-learning development strategy for the Al-Balqaʼ Applied University. A learning management system is crucial for teaching and learning, and with technological improvements, e-learning is becoming the norm in every country. As a result, developing and upgrading e-learning technologies to aid the educational process and improve students’ learning experience is critical. The Al-Balqaʼ Applied University adopted Moodle as its primary e-learning system. As a result, the proposed e-learning system’s web application development will be based on Moodle. Web applications will take a two-stage approach: the first stage will be analyzing the current application to gain a complete understanding of the requirements for developing the e-learning system at the Al-Balqaʼ Applied University, and the second stage will be converting or translating these requirements into the proposed model based on the WebML method, which has seven steps.